2021
DOI: 10.21037/atm-21-3098
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a possible new target for diagnosis and treatment of postmenopausal osteoporosis through bioinformatics and clinical sample analysis

Abstract: Background: Postmenopausal osteoporosis, a common yet chronic systemic metabolic disease, has become a major public health problem due to life expectancy increasing around the world. The differentiation of mesenchymal stem cells (MSCs) into osteoblasts, and the differentiation of circulating monocyte cells into osteoclasts, play an important role in the balance of bone metabolism. However, when both undergo pathological changes, it can lead to abnormalities, resulting in osteoporosis. This study aims to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Furthermore, GO analysis revealed that bosutinib mainly influences extracellular structure organization, extracellular matrix organization, sterol biosynthetic process, secondary alcohol biosynthetic process, and cholesterol biosynthetic process (Figure B). Pathways enrichment analysis using GO and KEGG revealed several pathways related with bone metabolism or bone-related disease, including extracellular matrix organization, steroid biosynthesis, TNF signaling pathway, as well as starch and sucrose metabolism. PCA showed that the difference between groups is obvious (Figure S1D). Venn diagram analysis revealed that 382 and 297 genes were specifically expressed in hUCMSCs induced with and without bosutinib, respectively, with 10830 genes co-expressed between the two groups (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, GO analysis revealed that bosutinib mainly influences extracellular structure organization, extracellular matrix organization, sterol biosynthetic process, secondary alcohol biosynthetic process, and cholesterol biosynthetic process (Figure B). Pathways enrichment analysis using GO and KEGG revealed several pathways related with bone metabolism or bone-related disease, including extracellular matrix organization, steroid biosynthesis, TNF signaling pathway, as well as starch and sucrose metabolism. PCA showed that the difference between groups is obvious (Figure S1D). Venn diagram analysis revealed that 382 and 297 genes were specifically expressed in hUCMSCs induced with and without bosutinib, respectively, with 10830 genes co-expressed between the two groups (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…As an RBP, KHSRP was suggested to interact with lncRNAs in different tumors, and these interactions were involved in the regulation of downstream genes stability [ 43 , 44 ]. Notably, a previous report showed that KHSRP was dysregulated in MSCs and monocytes of PMOP patients, and presented the promising value for diagnosing and treating PMOP [ 45 ]. Here, our results further confirmed the low expression of KHSRP in PMOP patients and OVX mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed DEGs of patients with PMO ( 16 , 17 ). The present study focused on gene expression of PBMCs in patients with PMO because osteoclasts are differentiated from PBMCs ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…STITCH database was used to mine proteins that interact with bisphosphonates. Pathway enrichment data of the two analyses was combined, common Previous studies have analyzed DEGs of patients with PMO (16,17). The present study focused on gene expression of PBMCs in patients with PMO because osteoclasts are differentiated from PBMCs (18).…”
Section: Discussionmentioning
confidence: 99%